Tomosíntesis digital mamaria: puesta al día - López P., Alejandra; Castillo M., Ángela; Buttinghausen G., Valeria (Revista Hospital Clínico Universidad de Chile, 2016)
Conventional mammography has been used for decades for breast cancer screening. Its limitations are well known and are partly related to the fact that with conventional imaging, the three-dimensional volume of the breast is imaged and presented in a two-dimensional format, which leads to low sensitivity in detecting some cancers and high false-positive recall rates. Digital breast tomosynthesis consists in the acquisition of several low dose images from slightly different angles which are then sent to a computer that uses the data to generate 3-D images, providing breast images which are virtually free from superimposition. This is in particular important in cases of high mammographic density to differentiate real masses and architectural distortions from the overlying parenchyma. Digital breast tomosynthesis has shown decreased false-positive callback rates and increased rates of cancer detection, resulting in increased sensitivity and specificity, without a significant increase in the radiation dose.